Q Value Evaluation of Groundwater Quality under Plains in the Lower Reaches of the Yarkant River - DENG Ensong; LIU Yujiang; MA Ningxin; HUANG Shunyong (Renmin Zhujiang)
Evaluating groundwater quality plays an important role in the rational use of groundwater resources and groundwater environmental protection in the later period.Among 35 groups of groundwater quality test data taken in Tumxuk City,a plain area in the lower reaches of the Yarkant River in Xinjiang,the groundwater quality of 32 groups is Class V.A comprehensive evaluation model of groundwater quality is established by principal component analysis (PCA) with ten factors exceeding thresholds of Class V as evaluation indexes,including turbidity,total hardness,total dissolved solids,sulfates,chlorides,sodium,nitrites,fluorides,cadmium,and lead.Further,this paper proposes the method of calculating the Q value of groundwater quality and the fine classification standard of Q value,on the basis of which the groundwater in Class V can be sub-classified into V1—V4 classes.The evaluation results show that the groundwater quality in 2,24,and 6 groups is V2,V3,and V4,respectively. According to the Q value,the quality of groundwater can be judged directly,and it can provide a reference basis for selecting relatively good water quality from the same category of groundwater.